Anti-inflammatory actions of folate-functionalized bioactive ion-releasing nanoparticles imply drug-free nanotherapy of inflamed tissues. (July 2019) - Kim, Tae-Hyun; Kang, Min Sil; Mandakhbayar, Nandin; El-Fiqi, Ahmed; Kim, Hae-Won
Abstract: Inflammation prevailing conditions delay healing processes of damaged tissues, leading to a functional impairment. Although anti-inflammatory drugs are clinically available, they often cause unwanted side effects thus being considered suboptimal. Here we report drug-free synthetic nanoparticles that target and internalize pro-inflammatory cells and release ions, ultimately demonstrating profound anti-inflammatory functions. We introduce folate-functionalized bioactive glass nanoparticle BGN(F) that can bind to pro-inflammatory cells to endocytose and release ions. The folate-conjugation significantly enhanced the nanoparticle internalization to LPS-induced pro-inflammatory cells. The direct treatment of BGN(F) at proper doses (80–160 μg/mL) substantially down-regulated pro-inflammatory molecules, including TNF-α, IL-6, iNOS and COX-2, at both gene and protein levels. The phosphorylation of intracellular signaling molecules involved in the inflammatory events, such as p38 MAPK, ERK (1/2), SAPK/JANK, IκBα, and NF-κB, were significantly suppressed by the BGN(F) treatment. Furthermore, BGN(F) was potential to switch the macrophage polarization from M1 to M2. The released ions, not the physical interactions, of nanoparticles were observed to contribute in major part to the anti-inflammatory actions of BGN(F). The BGN(F), when locally administered to a Notexin-induced myoinjury tissue in mice, significantly down-regulated IL-6 and TNF-α, switched the macrophage phenotype from M1 to M2, and accelerated tissue healing. The current findings that demonstrate profound anti-inflammatory actions of BGN(F) in vitro and in vivo support their uses as novel drug-free nanotherapeutic platform for the treatment of inflamed tissues.